Enhancement in Curie Temperature of Yttrium Iron Garnet by Doping with Neodymium - Baños-López, Esperanza (Materials (Basel), 2018)
The effect of the substitution of Y(3+) by Nd(3+) on the structural and magnetic properties of neodymium-doped yttrium iron garnet, Nd(x)Y(3−x)Fe(5)O(12) with x in the range of 0–2.5, is presented. Oxide powders of Fe(2)O(3), Nd(2)O(3), and Y(2)O(3) were mixed in a stoichiometric ratio and milled for 5 h using high-energy ball milling, before being uniaxially pressed at 900 MPa and annealed at 1373 K for 2 h to obtain Nd(x)Y(3−x)Fe(5)O(12) (0 ≤ x ≤ 2.5). It was found that the mechanical milling of oxides followed by annealing promotes the complete structural formation of the garnet structure. Additionally, the X-ray diffraction patterns confirm the complete introduction of Nd(3+) into the garnet structure with a neodymium doping concentration (x) of 0–2.0, which causes a consistent increment in the lattice parameters with the Nd(3+) content. When x is higher than 2.0, the yttrium orthoferrite is the predominant phase. Besides, the magnetic results reveal an increase in the Curie temperature (583 K) as the amount of Nd(3+) increases, while there was enhanced saturation magnetization as well as modified remanence and coercivity with respect to non-doped YIG.